Human Beta Defensin 2 Ameliorated Alcohol-Associated Liver Disease in Mice - Warner, Jeffrey B.; Larsen, Ida S.; Hardesty, Josiah E.; Song, Ying L.; Warner, Dennis R.; McClain, Craig J.; Sun, Rui; Deng, Zhongbin; Jensen, Benjamin A. H.; Kirpich, Irina A. (Frontiers in Physiology, 2022)
Alcohol-associated liver disease (ALD) is a prevalent liver disorder and significant global healthcare burden with limited effective therapeutic options. The gut-liver axis is a critical factor contributing to susceptibility to liver injury due to alcohol consumption. In the current study, we tested whether human beta defensin-2 (hBD-2), a small anti-microbial peptide, attenuates experimental chronic ALD. Male C57Bl/6J mice were chronically fed an ethanol (EtOH)-containing diet for 6 weeks with daily administration of hBD-2 (1.2mg/kg) by oral gavage during the final week. Two independent cohorts of mice with distinct baseline gut microbiota were used. Oral hBD-2 administration attenuated liver injury in both cohorts as determined by decreased plasma ALT activity. Notably, the degree of hBD-2-mediated reduction of EtOH-associated liver steatosis, hepatocellular death, and inflammation was different between cohorts, suggesting microbiota-specific mechanisms underlying the beneficial effects of hBD-2. Indeed, we observed differential mechanisms of hBD-2 between cohorts, which included an induction of hepatic and small intestinal IL-17A and IL-22, as well as an increase in T regulatory cell abundance in the gut and mesenteric lymph nodes. Lastly, hBD-2 modulated the gut microbiota composition in EtOH-fed mice in both cohorts, with significant decreases in multiple genera including Barnesiella, Parabacteroides, Akkermansia, and Alistipes, as well as altered abundance of several bacteria within the family Ruminococcaceae. Collectively, our results demonstrated a protective effect of hBD-2 in experimental ALD associated with immunomodulation and microbiota alteration. These data suggest that while the beneficial effects of hBD-2 on liver injury are uniform, the specific mechanisms of action are associated with baseline microbiota.